HIV enteropathy: HAART reduces HIV-induced stem cell hyperproliferation and crypt hypertrophy to normal in jejunal mucosa. Issue 1 (23rd July 2013) - Batman, Philip A; Kapembwa, Moses S; Belmonte, Liliana; Tudor, Gregory; Kotler, Donald P; Potten, Christopher S; Booth, Catherine; Cahn, Pedro; Griffin, George E
Abstract : Objective: To analyse the structural and kinetic response of small intestinal crypt epithelial cells including stem cells to highly active antiretroviral therapy (HAART). Design: Crypt size and proliferative activity of transit and stem cells in jejunal mucosa were quantified using morphometric techniques. Methods: Crypt length was measured by counting the number of enterocytes along one side of a number of crypts in each biopsy specimen and the mean crypt length was calculated. Proliferating crypt cells were identified with MIB-1 monoclonal antibody, and the percentage of crypt cells in proliferation was calculated at each cell position along the length of the crypt (proliferation index). Data were obtained from 9 HIV-positive test patients co-infected with microsporidia, 34 HIV-positive patients receiving HAART and 13 control cases. Results: Crypt length was significantly greater in test patients than in controls, but crypt length in patients receiving HAART was normal. The proliferation index was greater in test subjects than in controls in stem and transit cell compartments, and was decreased in patients treated with HAART only in the stem cell region of the crypt. Conclusions: Villous atrophy in HIV enteropathy is attributed to crypt hypertrophy and encroachment of crypt cells onto villi. HAART restores normal crypt structure by inhibition of HIV-driven stem cell hyperproliferation at the crypt bases.